Contemporary social philosophy - "Graham, Gordon." (Oxford, 1988)
Gordon Graham, Princeton Theological Seminary$1 (Bs Henry Luce III Professor of Philosophy and the Arts, earned MA degrees from the University of St. Andrews and the University of Durham, and a PhD degree from the University of Durham. He was elected a Fellow of the Royal Society of Edinburgh, Scotland$1 (Bs premier academy of letters, in 1999. He is an ordained Anglican priest, and his areas of academic interest include aesthetics, moral philosophy, philosophy of religion, and the Scottish philosophical tradition. He is editor of the Journal of Scottish Philosophy and a founding editor of the Kuyper Center Review (less)s
Keywords: Social science-Philosophy